Effect Of Organizational And Citizenship Behavior Sharing Knowledge Of Employee Organizational Commitments - Hasrudy Tanjung; Linzzy Pratami Putri (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to investigate and analyze the Effect of Organizational Citizenship Behavior and Knowledge Sharing together on Organizational Commitment of Private Employees in Medan City. The approach I use is the associative research approach, quantitative. Population and sample in data analysis techniques using classical assumptions, multiple linear regression, t test, F test, and coefficient of determination. The object of study is permanent employees with a minimum service period of 2 years. The population is all private employees in the city of Medan, with the sample used is accidental sampling, where the sample is the employee who filled out the questionnaire. The results of this study indicate that organizational citizenship behavior (X1) towards organizational commitment (Y) has a positive and not significant effect. Knowledge sharing (X2) on organizational commitment (Y) has positive and significant effect. While organizational citizenship behavior (X1) and knowledge sharing (X2) together have a positive and significant effect on organizational commitment (Y).